2021
DOI: 10.1016/j.jpainsymman.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Dementia: Prevalence and Association With Neuropsychiatric Behaviors

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 81 publications
(79 reference statements)
2
42
0
2
Order By: Relevance
“…In the study of Lin et al, it was demonstrated that 49.07% of the elderly had experienced pain during the last year (23). Also, in the study of Atee et al, on 479 elderly people with dementia, it was shown that the prevalence of pain was 65.6% in this group (30), which is consistent with the results of prevalence of high pain in elderly with dementia.…”
Section: Discussionsupporting
confidence: 59%
“…In the study of Lin et al, it was demonstrated that 49.07% of the elderly had experienced pain during the last year (23). Also, in the study of Atee et al, on 479 elderly people with dementia, it was shown that the prevalence of pain was 65.6% in this group (30), which is consistent with the results of prevalence of high pain in elderly with dementia.…”
Section: Discussionsupporting
confidence: 59%
“…Of those, 5 studies demonstrated significant reductions in agitation and only one study used NPI as a measure of change (42). There are various triggers for BPSD such as staff practises, pain, discomfort, environmental stressors or over stimulation, and thus applying tailored multimodal interventions is the best practise approach (8,43).…”
Section: Discussionmentioning
confidence: 99%
“…BPSD is an umbrella term for a diverse range of neuropsychiatric (non-cognitive) symptoms that are either instigated by unmet needs (e.g., pain) or linked to psychiatric symptoms (e.g., hallucinations) (43,44). As such, it is difficult to untangle the impact of the programs unless we specifically focus on individual symptoms or subsyndromes.…”
Section: Discussionmentioning
confidence: 99%
“…The contention that BPSD represent a reaction to either unmet needs (e.g., pain), 2 or change in the environment (e.g., over‐ or under‐stimulation), 3 is relatively easy to support in most cases. 1 We accept that stress may arise when the environment places demands upon an individual that require an adaptive response.…”
Section: Bpsd—unmet Reactive And/or Organic?mentioning
confidence: 99%